Bedroom, Kitchen and Beyond: Women in the Survival and Advancement of the Ijaw Ethnic Nationality of Nigeria - Olali, Stephen Temegha (Researchparks Publishing, 2023)
Through historical times, women of the Ijaw ethnic nationality have proven by their activities and aptitudes, that the destiny of womanhood goes beyond the confines of the bedroom and the kitchen. This discourse opines that Ijaw women are cultured and have been champions in many endeavors of life. The discourse examines the Ijaw women from ancient to modern times.